Bastion-Making in Santurce: LaGoyco Takes on Grief and Recolonization. - DIAZ CARDONA, REBIO (Centro Journal)
Taller Comunidad LaGoyco is a community organization operating in the Machuchal sector of Santurce, a district of San Juan experiencing gentrification. In the years since Hurricane María the group has transformed a vacant school in the area into a vibrant community center, helping the neighborhood respond to a host of needs and challenges. In this essay I offer an account of the story of LaGoyco with a focus on the organization's spatial practices, showcasing their work as a case study in grassroots placemaking in a post-disaster context. I argue that the LaGoyco working group engages in a kind of placemaking I call bastion-making, in which a community facing threats on multiple flanks responds by forging sociospatial structures that afford protection on multiple fronts. Building on interviews and participant observation, I present a series of vignettes highlighting key "spatial" turning points in the story of the organization. I draw from environmental psychology and actor-network theory to conceptualize bastion-making as a spatial justice-oriented form of placemaking, using the story of LaGoyco as an example of space-conscious autogestión intent on defending the right to the city in the context of intersecting crises that characterized the period in which the project took shape. In the last section, I focus on the contribution of one of LaGoyco's main shapers, the late musician and activist Héctor "Tito" Matos, to offer a more personal reflection on the role of individual agency in placemaking, in a context where the threat of displacement is experienced as a form of recolonization.